(untitled) (Sumatera Medical Journal, 2023)
Background: Traditional herbal medicine has been used for centuries and remains an important component of healthcare globally. However, the therapeutic effectiveness of many herbal remedies is often limited by issues such as poor bioavailability, low stability, and lack of targeted delivery. In recent years, the application of nanotechnology has emerged as a promising strategy to enhance the efficacy of herbal medicines. Nano drug delivery systems involve the use of nano-sized carriers such as liposomes, polymeric nanoparticles, solid lipid nanoparticles, and nanoemulsions to encapsulate and deliver herbal bioactive compounds in a controlled and targeted manner. Objective: This review highlights recent advancements in nanotechnology-based delivery systems for herbal medicine and explores their potential applications in treating diseases such as cancer, cardiovascular conditions, neurodegenerative disorders, and inflammatory illnesses. Results: These systems improve solubility, protect compounds from degradation, prolong circulation time, and enable targeted delivery to specific tissues or cells. Moreover, nanocarriers can support the combination of multiple herbal ingredients, facilitating synergistic effects and personalized therapeutic approaches. Conclusion: The integration of nanotechnology and herbal medicine offers new possibilities in modern healthcare, although further research is required to address challenges in clinical translation, safety, and large-scale production. Collaboration among scientists, clinicians, and herbalists will be crucial in advancing this innovative field.